User perceptions of Islamic website (I-webs) - S. Abd. Aziz, Madihah; Othman, Marini (The Institute of Electrical and Electronics Engineers, Inc., 2016)
Despite attending face-to-face meetings with the Muslim scholars, the Islamic Websites (I-webs) has been one of the most influential mediums of communication for Muslims across the globe to find information about Islam, and to share the knowledge they learned to both Muslims and non-Muslims. Realizing the significant impact of I-webs in spreading da'wah, it is imperative for the researchers understand the perception of our younger generation about I-webs as the source of information. This paper explores the Muslim Youths' perception of I-webs among undergraduate students aged between 19 to 22 years old. I-webs were evaluated using Islamic Website Evaluation Guidelines (IWEG) survey instrument. The outcome of this research will be used to further improve the design of I-webs to attract more users, particularly among the younger generation to deliver messages on the beauty of Islam.